Explanatory model of the impact of globalization on entrepreneurial education: Global policies, entrepreneurial behaviors and international networks - Jardim, Jacinto (REGEPE Entrepreneurship and Small Business Journal, 2024)
Objective: explain the impact of globalization on the emergence of trends for entrepreneurial education. Method: a theoretical-reflective review of the literature was carried out, using thematic analysis, to answer the research questions; 51 articles collected from Scopus, WOS and Google Scholar were analyzed and organized into three thematic groups. Originality/Relevance: there was a lack of a qualitative study that, based on literature, demonstrated the impact of entrepreneurial education. Results: three thematic dimensions were recognized that explain the impact of entrepreneurial education: identifying socio-educational contexts and problems, defining global educational policies, and creating international research and development networks. Theoretical/methodological contributions: these explanatory dimensions of the impact of entrepreneurial education made it possible to specify the following specific contributions: educational, labour and social policies; behaviours related to the ability to think creatively, act with initiative and make things happen; and international networks that stimulate entrepreneurial skills, employability and social cohesion.